Do positive events and emotions offset the difficulties of stressful life events? A daily diary investigation of depressed adults. (February 2022) - Panaite, Vanessa; Yoon, Sunkyung; Devendorf, Andrew R.; Kashdan, Todd B.; Goodman, Fallon R.; Rottenberg, Jonathan
Abstract: Can positive events and positive emotions reduce the impact of a stressful event in people with depression? In previous research, studies have found that positive events and positive affect (PA) that co-occur with daily stressors can reduce – or offset – the emotional impact of the stressors. However, this effect has not been examined in people with depression, an emotional disorder characterized by higher levels of negative affect (NA) and lower levels of PA. This study examined whether depression is an individual difference variable in affective offset through testing whether depression reduces or eliminates affective offset. Using a nationally representative sample with daily assessments across eight days, we examined reports of positive events, stressors, and PA and NA from 121 adults with a depression diagnosis versus 839 adults with no depression symptoms. For depressed persons, when a stressor occurred, same day number of positive events, but not PA, offset next day NA. At the same time, depressed participants who reported higher average daily PA also reported lower NA the day after a stressor occurred. Our study provides evidence that some depressed persons exhibit affective offset and some depressed persons do not. We offer several explanations for the heterogeneous reactions of depressed individuals.